2022
DOI: 10.23865/ntpk.v8.3433
|View full text |Cite
|
Sign up to set email alerts
|

Undervisning om samiske temaer i skolen – betydninga av kompetanse og urfolksperspektiv for en inkluderende praksis

Abstract: Skolen legger føringer for undervisning om samisk historie, språk, kultur, samfunn og rettigheter. I denne artikkelen undersøker vi erfaringer med disse temaene gjennom intervjuer med laerere fra seks ulike skoler i Norge; tre i Nord-Norge og tre på Østlandet. Laerernes praksis påvirkes av samspillet mellom blant annet laereplaner, laeremidler, stedstilhørighet og perspektivering. Disse kan forstås som forutsetninger for å forankre samisk tematikk i undervisningspraksis. Vi argumenterer for at det foregår ei u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 5 publications
(7 reference statements)
1
12
0
Order By: Relevance
“…The partial implementation of Sámi aspects particularly found outside the Saepmie region by Evju and Olsen (2022) and Lile (2011) are in line with the findings of Kavli (2019). Kavli (2019) found that deprioritizing Sámi topics in teaching happens more frequently outside the administrative areas of the Sámi language where teachers obtain less cultural knowledge and support from Sámi institutions.…”
Section: Introduction 1sámi and Indigenous Topics In The Norwegian Sc...supporting
confidence: 90%
See 4 more Smart Citations
“…The partial implementation of Sámi aspects particularly found outside the Saepmie region by Evju and Olsen (2022) and Lile (2011) are in line with the findings of Kavli (2019). Kavli (2019) found that deprioritizing Sámi topics in teaching happens more frequently outside the administrative areas of the Sámi language where teachers obtain less cultural knowledge and support from Sámi institutions.…”
Section: Introduction 1sámi and Indigenous Topics In The Norwegian Sc...supporting
confidence: 90%
“…When discussing colonialization, the textbooks did not contextualize this to the Sámi people in Norway, but they rather connected colonialization to foreign and overseas indigenous people. These textbooks were, however, published before the present curriculum, which was implemented in 2020 (Opplaeringslova 2020), and Sámi cultural, historical, and societal perspectives are strengthened in the core values of the present curriculum compared to the previous one from 2006 (Evju and Olsen 2022).…”
Section: Sámi Content In Teaching Aidsmentioning
confidence: 99%
See 3 more Smart Citations